2008
DOI: 10.1021/je700685q
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Density of Plant Oils under High Pressure

Abstract: The effect of pressure on the thermal conductivity and density of olive, safflower, linseed, and castor oils in the temperature range of (283 to 333) K and pressures up to 400 MPa was studied. The thermal conductivity measurements were carried out using a transient hot-wire method with an estimated uncertainty of 2.7 mW·m−1·K−1. The density of olive oil was determined within an uncertainty of 0.3 % by a Jamin interferometer. Results reveal an increase in the thermal conductivity and density with pressure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…Thermal conductivity of 10 % (w/v) sucrose solution and tomato purée (5.04 % solid content) closely followed the thermal conductivity values of water. Similar observations were also made by Werner et al (2008) who reported that thermal conductivity of sugar solutions was primarily a function of applied pressure and mass fraction. In the case of honey, the main components were glucose (35.7 %), fructose (41.0 %), galactose (3.0 %) and water (17.1 %) (USDA, National Nutrient Data Base).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Thermal conductivity of 10 % (w/v) sucrose solution and tomato purée (5.04 % solid content) closely followed the thermal conductivity values of water. Similar observations were also made by Werner et al (2008) who reported that thermal conductivity of sugar solutions was primarily a function of applied pressure and mass fraction. In the case of honey, the main components were glucose (35.7 %), fructose (41.0 %), galactose (3.0 %) and water (17.1 %) (USDA, National Nutrient Data Base).…”
Section: Resultssupporting
confidence: 85%
“…Increase in thermal conductivity values of foods with increasing pressure (Fig. 4) has also been reported earlier (Denys and Hendrickx 1999;Ramaswamy et al 2007;Zhu et al 2008;Werner et al 2007Werner et al , 2008. Pressure dependency of thermal conductivity seems to be a function of compressibility of materials (Bridgman 1923;Ross et al 1984).…”
Section: Resultssupporting
confidence: 82%
“…transmitting medium, food product). Even though the thermophysical properties of water (commonly used as pressure medium in industry) and of a limited range of food (model) systems, pressure media and insulating plastics under high pressure are known (Denys and Hendrickx, 1999;Forst et al, 2002;Otero and Sanz, 2003;Rasanayagam et al, 2003;Werner et al, 2007Werner et al, , 2008Knoerzer et al, 2009), the knowledge of the combined effect of temperature and pressure on these properties is far from complete (Otero and Sanz, 2003). In addition, numerical simulation demands high computational power and is case-dependent, thus requiring re-evaluation if, for example, the load of the pressure vessel is changed .…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil has been a subject of intensive research, also with regard to the effect of pressure because of its importance to the food industry. Several physical properties such as: thermal conductivity and density [12], ultrasonic attenuation coefficient [13], ultrasonic velocity [14], PVT characteristic up to 150 MPa [15], volumetric properties [16] and thermal diffusivity [17]have been presented by various authors, but none of them have reported pressure-induced phase transition. Some suggestions appeared in the work [18], but the results obtained were ambiguous.…”
Section: Introductionmentioning
confidence: 99%